Functionalized Scaffold and Barrier Membrane with Anti-BMP-2 Monoclonal Antibodies for Alveolar Ridge Preservation in a Canine Model. (23rd September 2020) - Min, Seiko; Kim, Taewan; Kim, Oksu; Goncalo, Carames; Utsunomiya, Tadahiko; Matsumoto, Takashi; Kuyama, Kayo; Angelov, Nikola
Abstract : Introduction . The aim of this study was to investigate the ability of anti-bone morphogenetic protein 2 monoclonal antibody (anti-BMP-2 mAb) to functionalize scaffolds to mediate bone regeneration in a canine model. Materials and Methods . The mandibular right premolar 4 (PM4) was extracted in eight beagle dogs and grafted with anti-BMP-2 mAb+anorganic bovine bone mineral with 10% collagen (ABBM-C) and porcine bilayer native collagen membrane (CM). The ABBM-C and CM were functionalized with either anti-BMP-2 mAb (test group) or an isotype matched control mAb (control group). Animals were euthanized at 12 weeks for radiographic, histologic, and histomorphometric analyses. Outcomes were compared between groups. Results . 3D imaging using cone beam computed tomography (CBCT) revealed that sites treated with ABBM-C and CM functionalized with anti-BMP-2 mAb exhibited significantly more remaining bone width near the alveolar crest, as well as buccal bone height, compared with control groups. Histologic and histomorphometric analyses demonstrated that in anti-BMP-2 mAb-treated sites, total tissue volume was significantly higher in the coronal part of the alveolar bone crest compared with control sites. In anti-BMP-2 mAb-treated sites, bone formation was observed under the barrier membrane. Conclusion . Functionalization of the ABBM-C scaffold and CM appeared to have led to bone formation within healing alveolar bone sockets.